Characterization of β-cyclodextrin/myrtenol complex and its protective effect against nociceptive behavior and cognitive impairment in a chronic musculoskeletal pain model. (15th September 2020) - Heimfarth, Luana; dos Anjos, Klécia Santos; de Carvalho, Yasmim Maria Barbosa Gomes; dos Santos, Bruno Lucena; Serafini, Mairim Russo; de Carvalho Neto, Antônio Guilherme; Nunes, Paula Santos; Beserra Filho, José Ivo Araújo; da Silva, Sara Pereira; Ribeiro, Alessandra Mussi; Bezerra, Daniel Pereira; Marreto, Ricardo Neves; et al.
Highlights: β-cyclodextrin/myrtenol (β-CD/MYR) complex was done by slurry complexation method. β-CD/MYR complex reduced mechanical hyperalgesia in animal model. β-CD/MYR complex showed anxiolytic-like effect in animal model of fibromyalgia. β-CD/MYR complex prevented cognitive impairment caused by acid saline injection. These effects seemed to be related to the maintenance of redox homeostasis. Abstract: Myrtenol has gained wide interest because of its pharmacological profiles, mainly for treatment of chronic diseases. To improve the solubility of myrtenol, the formation of inclusion complexes with β-cyclodextrin was performed by physical mixture, kneading process or slurry complexation (SC) methods and characterized using thermal analysis, XRD, SEM and NMR. From these results, myrtenol complexed by SC was successfully complexed into β-cyclodextrin cavity. The interaction between myrtenol and β-cyclodextrin was confirmed by molecular docking. Hence, the SC β-cyclodextrin-myrtenol complex was evaluate for its anti-hyperalgesic, anxiolytic and antioxidant activity in a fibromyalgia model. Results show that myrtenol and β-cyclodextrin form a stable complex and have anti-hyperalgesic effect, improve the cognitive impairment caused and have an anxiolytic-like effect. Furthermore, the β-cyclodextrin/myrtenol complex decrease lipoperoxidation, increased catalase activity and a reduce SOD/CAT ratio. Therefore, β-cyclodextrin/myrtenol complex reduce painful behavior, improves motor skills and emotional behavior and decreases oxidative stress in a fibromyalgia model.